2014
DOI: 10.1590/s0102-09352014000100020
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive efficiency of adult and prepubertal goats subjected to repeated follicular aspiration

Abstract: Reproductive efficiency of adult and prepubertal goats subjected to repeated follicular aspiration [ ABSTRACTThe objective of this study was to assess the reproductive response of adult and prepubertal goats subjected to repeated laparoscopic ovum pick-up (LOPU). The study animals were divided into two groups, specifically, adult nanny goats (GA, n=10) and prepubertal nanny goats (GP, n=10), which were subjected to estrous synchronization and ovarian stimulation for LOPU. Both groups underwent six LOPU proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Several authors reported oocyte recovery rates ranging from 16 to 98% (Alberio et al, 2002;Gibbons et al, 2007;Teixeira et al, 2011;Cordeiro et al, 2014) in small ruminants. Due to the shortage of LapOPU data in rodents, it can be assumed that the recovery rate achieved in our study (32.56±27.32%) is in accordance with what Rodríguez et al (2006) considered normal (from 32 to 90%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported oocyte recovery rates ranging from 16 to 98% (Alberio et al, 2002;Gibbons et al, 2007;Teixeira et al, 2011;Cordeiro et al, 2014) in small ruminants. Due to the shortage of LapOPU data in rodents, it can be assumed that the recovery rate achieved in our study (32.56±27.32%) is in accordance with what Rodríguez et al (2006) considered normal (from 32 to 90%).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic ovum pick-up (LapOPU) used for in vitro production (IVP) is one of the leading reproductive biotechniques in assisted reproduction, highlighted for being less invasive, provide a quicker recovery and the possibility of being held several times in the same female as already described in some domestic species (Teixeira et al, 2011;Cordeiro et al, 2014;Padilha et al, 2014;Teixeira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported the occurrence of intraperitoneal adhesions on the reproductive tract of 15% of goats following ovum pick-up, even though the organs were rinsed with heparin solution following surgery (Cordeiro et al 2014). Unilateral and bilateral ovarian adhesions were reported in ewes following 10 sessions of laparoscopic OPU, which were performed at seven-day intervals (Stangl et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although adhesions formed over the ovaries, those were considered easy to dissect and irrelevant for repeated OPU. The use of other anti-adhesion therapies, such as a heparin-based one (Baldassarre and Karatzas 2004;Cordeiro et al 2014) or carboxymethylcellulose solutions (Ewoldt et al 2004) have been recommended; however, even these solutions were not fully efficient in preventing adhesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation